Coccidioides posadasii in a Dog With Cervical Dissemination Complicated by Esophageal Fistula - Izquierdo, Adrien; Jaffey, Jared A.; Szabo, Stephanie; Struthers, Jason; Okwumabua, Ogi; Hostnik, Eric T.; Ohkura, Mana; Trinh, Hien; Shubitz, Lisa F.; Orbach, Marc J.; White, Mary E. (Frontiers in Veterinary Science, 2020)
A 5-year-old male, neutered mixed breed dog with a history of a mass with an associated draining tract on the ventral cervical region was diagnosed with an esophageal fistula. The dog exhibited serosanguinous discharge from the draining tract, with enlarged left superficial cervical and mandibular lymph nodes, and was reported to have difficulty with deglutition of solid foods. Computed tomography revealed a communication of the draining tract with the esophagus along with enlargement of the left lateral retropharyngeal, left medial retropharyngeal, and mandibular lymph nodes. This prompted surgical exploration and debridement of the site, with closure of the esophageal fistula. Histopathology of thyroid gland, skeletal muscle, and adipose tissue obtained during surgical exploration showed spherules consistent with Coccidioides spp. infection. Antibody titers performed post-operatively were consistent with an active Coccidioides spp. Infection. By fungal culture and subsequent PCR and DNA sequencing, C. posadasii was identified as the species infecting the dog. Over the course of 85 days of antifungal therapy, discharge from the draining tract, lymphadenomegaly, and cutaneous and subcutaneous nodules resolved. In conclusion, this is the first reported case of disseminated coccidioidomycosis to the cervical region of a dog with involvement of the thyroid gland, skeletal muscle, adipose tissue, connective tissue, and secondary esophageal fistula. Coccidioides spp. infections should be considered a differential diagnosis in unusual cases for dogs that live in or have traveled to endemic areas.